2006
DOI: 10.1057/palgrave.jibs.8400188
|View full text |Cite
|
Sign up to set email alerts
|

National culture and financial systems

Abstract: Countries differ in the way their financial activities are organized. In Anglo-Saxon countries such as the US and the UK financial systems are dominated by stock markets, whereas in continental Europe and Japan banks play a predominant role. Why do countries differ in the configuration of their financial systems? We argue that national culture plays a significant role. We find that countries characterized by higher uncertainty avoidance are more likely to have a bank-based system. Journal of International Busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
270
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(292 citation statements)
references
References 28 publications
15
270
2
5
Order By: Relevance
“…Third, although Nigerian affiliates of foreign professional bodies, such as the Association of Certified Fraud Examiners (ACFE) and the Institute of Certified Forensic Accountants (ICFA) have sprung up, the extent to which they are meaningfully engaged in anti-fraud investigations and litigation support cases is minimal. Studies have shown that education has a positive, albeit moderate, direct effects on corruption [43]. Above all, the tolerance of African culture to corruption can be ebbed and the beneficial effects of education on corruption enhanced with increased FDI flows and their interaction effects (ibid.…”
Section: Concluding Remarks and Recommendationmentioning
confidence: 99%
“…Third, although Nigerian affiliates of foreign professional bodies, such as the Association of Certified Fraud Examiners (ACFE) and the Institute of Certified Forensic Accountants (ICFA) have sprung up, the extent to which they are meaningfully engaged in anti-fraud investigations and litigation support cases is minimal. Studies have shown that education has a positive, albeit moderate, direct effects on corruption [43]. Above all, the tolerance of African culture to corruption can be ebbed and the beneficial effects of education on corruption enhanced with increased FDI flows and their interaction effects (ibid.…”
Section: Concluding Remarks and Recommendationmentioning
confidence: 99%
“…1 See Kwok and Tadesse (2006) and Beck, Demirguc-Kunt and Levine (2003) For example, ROA is measured by the ratio of net income to total assets multiplied by 100. 8 The ordered probit model also produces a second set of estimates.…”
Section: Discussionmentioning
confidence: 99%
“…When people talk about culture, they talk about a way of life, what people believe, and how they apply that to develop their regulations, organisations and institutions. Kwok and Tadesse (2005) [21] argue that countries differ in the configuration of their financial systems because they are different in terms of their national cultures.…”
Section: Religious and Cultural Factorsmentioning
confidence: 99%
“…The financial systems in Australia, the UK and the USA are very similar and are dominated by their stock markets [21] and although UAE financial systems have some similarities with these countries, there are important differences. These differences play an important role in how the country implements its AML/CFT system.…”
Section: Socio-economic and Financial Factorsmentioning
confidence: 99%